2013
DOI: 10.1002/anie.201303483
|View full text |Cite
|
Sign up to set email alerts
|

A Mild, One‐Pot Stadler–Ziegler Synthesis of Arylsulfides Facilitated by Photoredox Catalysis in Batch and Continuous‐Flow

Abstract: Visible advance: A mild, one-pot Stadler-Ziegler process for C-S bond formation has been developed. The method employs the photoredox catalyst [Ru(bpy)3Cl2]⋅6 H2O irradiated with visible light. A variety of aryl-alkyl and diaryl sulfides were prepared from readily available arylamines and aryl/alkylthiols in good yields. The use of a photo microreactor led to a significant improvement with respect to safety and efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(96 citation statements)
references
References 68 publications
2
92
0
2
Order By: Relevance
“…[20] A one-pot procedure for aryl sulfide formation was needed because the synthesis of aryl sulfides was a multistep process that required handling of diazonium salts. To make an aryl sulfide, an aryl amine is converted into a diazonium salt by nitrosation.…”
Section: Continuing Development Of Visible-light Photoredox Flow Chmentioning
confidence: 99%
“…[20] A one-pot procedure for aryl sulfide formation was needed because the synthesis of aryl sulfides was a multistep process that required handling of diazonium salts. To make an aryl sulfide, an aryl amine is converted into a diazonium salt by nitrosation.…”
Section: Continuing Development Of Visible-light Photoredox Flow Chmentioning
confidence: 99%
“…4 In 2013, Noël and co-workers reported a one-pot Stadler–Ziegler process to form C–S bonds by employing Ru(bpy) 3 Cl 2 ·6H 2 O as a photoredox catalyst. 5 Dual photoredox/Ni-catalyzed cross-coupling of thiols with (hetero)aryl halides was then developed in 2016. 6 More recently, [ fac -Ir(ppy) 3 ] was implemented to catalyze the arylation of thiols with aryl halides without the need for a nickel catalyst.…”
mentioning
confidence: 99%
“…It has been shown by several authors that hazardous intermediates can be generated in situ and subsequently reacted away in a follow up reaction. 143 Kappe et al demonstrated elegantly this principle in the synthesis of tetrazoles ( Figure 14). 144 Hydrazoic acid (HN3), an extremely toxic compound, was prepared in situ in a microreactor and consumed immediately by reaction with a nitrile to prepare the corresponding tetrazoles.…”
Section: Safety Aspectsmentioning
confidence: 95%